Penguatan Ekowisata dan Pemberdayaan Lokal dalam Rangka Pembentukan Pariwisata Berkelanjutan di Kawasan Pantai Mutun, Pesawaran - Rinaldi Bursan; Dina Safitri; Aida Sari; Driya Wiryawan; Prakarsa Panjinegara; Faila Shofa (Lembaga Pengembangan Kinerja Dosen, 2025)
Sustainable tourism aims to maximize the potential of travel destinations while maintaining a careful balance between social, economic, and environmental factors, and coastal tourism such as that found at Mutun Beach in Lampung illustrates both the promise and the urgency of this approach. Coastal tourism is one of the fastest-growing segments of the global travel industry, offering visitors natural beauty, recreational activities, and cultural experiences that generate significant income for local economies. In Indonesia, beaches are major attractions that can boost regional development through job creation, small business opportunities, and improved infrastructure. Mutun Beach, a well-known coastal destination on the southern coast of Sumatra, contributes greatly to the Regional Original Income (PAD) of Lampung Province and provides livelihoods for surrounding communities. Yet despite its popularity, the area continues to face persistent problems such as weak administrative management, limited community participation, inadequate facilities, and signs of environmental degradation, all of which threaten its long-term sustainability. This service project therefore focuses on designing a comprehensive plan for sustainable tourism growth at Mutun Beach for the 2025–2030 period. A participatory strategy is employed through Focus Group Discussions (FGD) involving local government, tourism stakeholders, community members, academics, and potential investors to ensure inclusive decision-making. The resulting five-stage roadmap emphasizes strengthening tourism regulations, constructing eco-friendly infrastructure, empowering residents with training and entrepreneurial opportunities, creating tourism products that highlight environmental and cultural values, and adopting digital marketing to reach broader audiences. Success indicators include increased regional revenue, rising visitor numbers, higher tourist satisfaction, and measurable improvements in coastal environmental health. Implementing this roadmap is urgent because coastal tourism directly supports economic growth, provides steady employment, and safeguards natural resources, ensuring that Mutun Beach remains both competitive and environmentally resilient for generations to come.